Post-exposure prophylaxis after sexual exposure (PEPSE) awareness in an HIV-positive cohort. (January 2014) - Joshi, Manavi; Basra, Amardeep; McCormick, Claire; Webb, Helen; Pakianathan, Mark
Post-exposure prophylaxis after sexual exposure (PEPSE) awareness was audited in an HIV-positive cohort. A total of 403 out of 828 (48.7%) patients were PEPSE aware. Patients diagnosed post-2006 were more PEPSE aware; 57.2% vs. 44.2% ( p = 0.0004). Men who have sex with men (MSM) were more PEPSE aware; 65.8% vs. 39.1% in heterosexuals ( p < 0.0001).Younger patients, 68.1% aged 19–34 were PEPSE aware vs. 45.7% in those >35 years ( p < 0.0001). In the 534 patients reporting sexual activity within the last year, awareness was 57.5%. In the 216 patients 'sometimes' or 'never' using condoms, awareness was 42.6%. In the 78 (9.4%) patients with detectable viral loads (>400 copies/mL), awareness was 64.1%. Overall, PEPSE awareness was unexpectedly low. MSM, younger patients, and those diagnosed after 2006 were significantly more likely to be PEPSE aware. More than one in three patients with detectable viraemia were PEPSE unaware.